Digital Platforms and the Press - Meese, James (2023)
James Meese argues that there is a growing risk of a platform-dependent press, a development that threatens liberal democracies across the world. The book provides the first comprehensive account of how platform dependence manifests in the news media sector. Platform dependence is a concept used to describe what happens when businesses or an entire sector, become reliant on one or more digital platforms for its survival. The situation is occurring across the news industry, to the extent that it is difficult to imagine the production, distribution, and long-term survival of news in liberal democracies without the involvement of platforms.With governments, regulators and citizens increasingly concerned about platform power, Digital Platforms and the Press is the first book to highlight the long-term economic and social consequences of platform dependence for the news sector. Featuring a rich selection of case-studies and written in an accessible style, Digital Platforms and the Press provides a strong grounding in relevant debates for the interested student reader, and important takeaways for subject matter experts in journalism studies and media policy. Digital Platforms and the Press will be of interest to journalism and media policy scholars, other scholars in communication, as well as industry practitioners and policymakers.